Pengaruh Telekomunikasi dan Jaringan terhadap Yayasan Sahabat Yatim Indonesia (Asrama dan Kantor Layanan di Jl Nginden Semolo) - Dika Candra Laili; Hwihanus Hwihanus (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
Technological developments cannot be denied considering that from time to time technology continues to change in a more sophisticated direction. This development is based on human innovation and creativity. Technology plays a full role in human development today. In an era like this, maybe most people have technology, such as mobile phones. Mobile is a communication tool used to contact someone. Mobile was first discovered by Martin Cooper who was a Motorola employee on April 3 with the first model being the DynaTAC. At that time, DynaTAC could only function to receive phone calls and receive messages. But now the phone has many functions including, to send pictures, send sound, send addresses, and many others.